Aprendizagem: um estudo da contribuição da capacitação de motoristas de caminhão para a redução dos custos operacionais da frota - Silva, Waldir Barbosa da (2007)
The purpose of this dissertation is to study the contribution of actions of truck drivers training, searching for operational costs reduction of the load carrier companies. For it, the learning theories provide support to the training actions analysis, notably the social cognitive theory of Albert Bandura (1986), which explains human actuation through a reciprocity model in which the behavior, the cognitive personal factors and the environmental events interact among themselves in a determinant way. It is an approach between the two mainly learning models, behaviorist and cognitivist. From the hypothesis that capacitated drivers contribute to companies competitiveness, indicators were defined to make possible that such subjective concepts could be understood and measured in an objective manner. The field research involved 105 vehicles with its respective drivers, distributed into 14 companies. The investigation was quantitative, with comparison of measuring data before and after training actions. It was tried this way to verify the statistic significance of the indicators variation between the two measurements. The work was developed in two steps. At the first step, the data were analyzed for the 14 companies as a whole. At the second step, an individual analysis was preceded, it means, route by route. The research revealed that to the sample as a whole and to 13 from 14 companies, when evaluated individually, the training actions produced changing at the drivers actuation manner with the vehicles being conducted in a safer and more economic way, consequently generating operational cost reduction to the companies